Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Kinerja Karyawan Cleaning Service pada PT ISS Indonesia Tangerang Selatan - Siti Dalsidah; Bilgah Bilgah (STIKes Ibnu Sina Ajibarang, 2024)
Employee performance is a good work success that has been achieved by employees through the activities that have been carried out. High performance indicates that employees successfully achieve the desired results, both in terms of quantity and quality of their work. It can be seen in increased productivity, service quality, customer satisfaction, and overall business results. This study aims to identify and analyze the effect of work discipline and work motivation on employee performance at PT Iss Indonesia. The research method used in this study is a quantitative method with a survey approach. Data was collected through questionnaires distributed to 68 employees at PT Iss Indonesia. The data analysis technique used is multiple linear regression analysis to determine the extent to which work discipline and work motivation affect employee performance. The results of this study indicate that work discipline has a significant effect of 0.812 or 81.2%, meaning that work discipline has a strong influence on employee performance. Motivation also has a significant effect of 0.832 or 83.2%, meaning that work motivation has a strong influence on employee performance. Simultaneously there is a positive and significant influence between work discipline and work motivation on employee performance at PT Iss Indonesia with a value of 87.5% and the remaining 12.5% is influenced by other factors.